2018
DOI: 10.1016/j.jaci.2017.08.031
|View full text |Cite
|
Sign up to set email alerts
|

LAIR-1 limits neutrophil extracellular trap formation in viral bronchiolitis

Abstract: Organization for Scientific Research. L.M. and L.B. have received funding for an investigator-initiated study to validate LAIR-1 as a therapeutic target in an experimental animal model of respiratory syncytial virus infection. Disclosure of potential conflict of interest: R. J. Geerdink's institution has received a grant from the Netherlands Organization for Scientific Research. The rest of the authors declare that they have no relevant conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 9 publications
3
32
0
Order By: Relevance
“…Conclusions: The immune inhibitory receptor LAIR‐1 limits the loss in body weight and neutrophil‐driven airway inflammation. Following our recent observations in humans, we conclude that LAIR‐1 is a promising target for pharmacological intervention in such pathologies.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Conclusions: The immune inhibitory receptor LAIR‐1 limits the loss in body weight and neutrophil‐driven airway inflammation. Following our recent observations in humans, we conclude that LAIR‐1 is a promising target for pharmacological intervention in such pathologies.…”
supporting
confidence: 79%
“…Therefore, factors that modulate the chemotaxis and activation of immune cells could be key in both the loss of body weight and inflammation. We recently identified the collagen receptor LAIR‐1 as a functional inhibitory receptor on airway‐infiltrated neutrophils in viral bronchiolitis patients . We hypothesize that LAIR‐1 regulates neutrophilic driven airway diseases and hence body weight loss.…”
mentioning
confidence: 99%
“…Additionally, LAIR-1 is absent in high-risk B cell chronic lymphocytic leukemia cells and LAIR-1 is downregulated on NK cells isolated from patients enduring a chronic active Epstein-Barr virus infection (20,21). More recently, it was shown that LAIR-1 is expressed on in vivo activated human neutrophils and that LAIR-1 suppresses neutrophil extracellular trap formation by airway-infiltrated neutrophils obtained from patients with respiratory syncytial virus (RSV) bronchiolitis (22). In mice, LAIR-1 limits neutrophilic airway inflammation (23).…”
Section: Introductionmentioning
confidence: 99%
“…Leucocyte‐associated Ig‐like receptor 1 (LAIR‐1), an inhibitory receptor that binds to native collagen, was shown to promote alternative activation of immunoregulatory, tissue‐restorative macrophages and inhibit pro‐inflammatory macrophage differentiation . LAIR‐1 signalling also reduced human neutrophil NET formation following ex vivo treatment with agonistic anti‐LAIR‐1 antibodies . Mice lacking tyrosine kinase collagen receptors discoidin domain receptors 1 and 2 (DDR1 and DDR2) are known to be protected from pulmonary fibrosis; however, these receptors also appear to regulate the function of immune cells.…”
Section: Effects Of Fibrosis On Innate Immunitymentioning
confidence: 99%
“…antibodies. 75 Mice lacking tyrosine kinase collagen receptors discoidin domain receptors 1 and 2 (DDR1 and DDR2) are known to be protected from pulmonary fibrosis 76,77 ; however, these receptors also appear to regulate the function of immune cells. DDR1 signalling is important in macrophage migration and production of NO, two functions key to the ability of macrophages to respond to pathogens.…”
Section: Effects Of Fibrosis On Innate Immunitymentioning
confidence: 99%